Dynamics of creatinine estimated glomerular filtration rate using one or more antiretrovirals that inhibit creatinine tubular secretion. (27th January 2021) - Perez Elias, Maria Jesus; Alejos, Belen; Gutierrez, Maria Mar; Crespo, Manuel; De Los Santos Gil, Ignacio; Ribera, Esteve; Galindo, Maria Jose; Lozano, Fernando; Payeras Cifre, Antonio; Boix, Vicente; Montero-Alonso, Marta; Sanz, José; et al.
Abstract: Background: Cobicistat, dolutegravir and rilpivirine are all modest inhibitors of proximal tubular creatinine secretion (IPTCrS) and hence a moderate and early non-progressive creatinine estimated glomerular filtration rate (Cr-eGFR) reduction has been observed in clinical trials. Data regarding the impact of combination of those drugs on Cr-eGFR, in the clinical practice, are scarcely known. Methods: Changes in Cr-eGFR after starting darunavir/cobicistat alone or in combination with dolutegravir and/or rilpivirine were studied in a nationwide retrospective cohort study of consecutive HIV-infected patients initiating darunavir/cobicistat. The relationship between Cr-eGFR changes over time and the use of darunavir/cobicistat alone or darunavir/cobicistat plus dolutegravir and/or rilpivirine adjusted by different HIV patient's characteristics, socio-demographics, HIV severity and use of tenofovir concomitant medication other than antiretrovirals was explored through univariate and multivariate analyses. Results: The analysis included 725 patients. At 48 weeks, the combination of two or more IPTCrS (darunavir/cobicistat with rilpivirine and/or dolutegravir) was associated with higher decreases in Cr-eGFR [adjusted median difference (±SD) –3.5 ± 1.6 (95% CI –6.6 to –0.3), P  =   0.047], and a decrease up to or higher than 15 mL/min/1.73 m 2 was more frequent [adjusted OR 3.233 (95% CI 1.343–7.782), P  =   0.009], with respect to darunavir/cobicistat alone. The Cr-eGFR changes between darunavir/cobicistat and darunavir/cobicistat with rilpivirine and/or dolutegravir showed more significant decreases in patients taking two or more IPTCrS at 12, 24 and 48 weeks. (ClinicalTrials.gov: NCT03042390). Conclusions: Concomitant use of darunavir/cobicistat plus IPTCrS dolutegravir, rilpivirine, or both produced an additive effect in the expected Cr-eGFR decrease.